Problem bank loans, conflicts of interest, and institutions - Breuer, Janice Boucher (Journal of Financial Stability, 2006)
I consider problem bank loans as the outcome of decisions made by banks in the dual role they serve as financial intermediaries. This dual role necessarily introduces conflicts of interest that can lead to bank mismanagement and consequently problem bank loans. Because bank activities take place within the tangible and intangible structure of institutions, institutions may affect the quality of bank loans. I consider legal, political, sociological, economic, and banking institutions and explore their contribution to problem bank loans. I find support that a variety of institutions impact the share of bank assets that are non-performing.